Electrodeposition and characterization of SN-BI lead-free soldier alloys / Goh YingXin - Goh, Ying Xin (2015)
Tin-bismuth eutectic alloy (Sn-58 wt.% Bi) is emerging as a potential lead-free solder alternative. The low melting temperature (138oC) of this alloy makes it a suitable candidate for higher level interconnections and for soldering heat sensitive components. Demands for high density interconnections led to the development of electroplating technique in soldering. In this work, a methane sulfonic acid (MSA) based plating bath is developed for the electrodeposition of Sn-Bi solder alloys. Composition control of the alloy is hampered by the large potential gap between the two elements. Electrolyte additives were incorporated to assist the simultaneous deposition of Sn and Bi. The effects of hydroquinone (HQ) and gelatin on the electroplating characteristics of Sn–Bi alloys were investigated. The effects of current density on the deposition behavior and composition of Sn-Bi alloy were investigated by galvanostatic studies. Microstructure and composition characterizations of as-electrodeposited and reflowed Sn-Bi alloys obtained at different current densities were performed by field emission scanning electron microscopy (FESEM) coupled with energy dispersive X-ray spectroscopy (EDS). The melting temperature of the near-eutectic Sn–Bi deposit was obtained by differential scanning calorimetry (DSC). The crystallinity of Sn–Bi deposits was also characterized with X-ray diffraction (XRD). The application of electroplated Sn-Bi solder alloys as solder joint materials were evaluated through their shear behaviour. The effects of reflow temperature on the microstructure and shear strength of Sn-Bi/Cu solder joints were studied. In the plating bath without additives and with either one of the additives, polarization studies showed that Bi deposits at about 25 to 45mV; while Sn deposits at about 410 to 420mV. The addition of HQ has a mild adsorption effect on the electrode surface. On the other hand, gelatin possesses mild complexing effect on Bi deposition. The synergistic effect of HQ and gelatin imposed a strong iv adsorption and complexing effect to reduce the large potential gap between Bi and Sn to only 243mV. With both HQ and gelatin added to the bath, co-deposition of Sn-Bi was achieved. Characterization of the electrodeposits indicated that Bi content in the alloys decreases with increasing current density. Near-eutectic Sn–60.75 wt.% Bi alloy was deposited from the bath containing both HQ and gelatin at a current density of 18mA cm-2. The extrapolated onset temperature from DSC analysis is around 137.4◦C, which is close to the eutectic melting temperature. The microstructure of the bulk solder and morphology of the intermetallic compound (IMC) changes with reflow temperature. The shear strength and elastic energy release, U of the joints increases with increasing reflow temperature. Fractographs of the failed joints shows the variation of fracture mechanisms under different reflow conditions. At low reflow temperatures, solder joints mainly failed with dimpled fracture. However at high reflow temperatures, Bi-rich phase served as a boundary to block the deformation of Sn-rich phase, causing the fracture path to deviate from the shear direction and resulted in an increase in strength and U value.